Homotypic cell membrane-camouflaged biomimetic PLGA nanoparticle loading triptolide for the treatment of hepatocellular carcinoma - Zhe Li; Jinshuai Lan; Ya Wu; Yue Ding; Tong Zhang (Taylor & Francis Group, 2024)
Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-associated death worldwide. Beside early detection, early diagnosis, and early surgery, it is urgent to try new strategies for the treatment of HCC. Triptolide (TPL) has been employed to treat HCC. However, its clinical applications were restricted by the narrow therapeutic window, severe toxicity, and poor water-solubility. In this study, we developed cancer cell membrane-camouflaged biomimetic PLGA nanoparticles loading TPL (TPL@mPLGA) with the homologous targeting property for the treatment of HCC. The TPL@mPLGA was successfully prepared with particle size of 195.5 ± 7.5 nm and zeta potential at −21.5 ± 0.2 mV with good stability. The drug loading (DL) of TPL@mPLGA was 2.94%. After Huh-7 cell membrane coating, the natural Huh-7 cell membrane proteins were found to be retained on TPL@mPLGA, thus endowing the TPL@mPLGA with enhanced accumulation at tumor site, and better anti-tumor activity in vitro and in vivo when compared with TPL or TPL@PLGA. The TPL@mPLGA showed enhanced anti-tumor effects and reduced toxicity of TPL, which could be adopted for the treatment of HCC.